The Efficacy of Er:YAG Laser in the Extraction of Impacted Third Molars: A Randomized Clinical Trial - Diana Sologova; Ekaterina Diachkova; Susanna Sologova; Elena Smolyarchuk; Arus Margaryan; Ekaterina Grigorevskikh; Pavel Petruk; Elizaveta Tumanova; Oxana Svitich; Svetlana Tarasenko (Dentistry Journal)
(1) Background: Impacted third molar extraction with a scalpel and rotary instruments is one of the most traumatic surgeries in dentistry. Therefore, it is necessary to discover less traumatic methods and instruments to reduce the risk of postoperative complications. (2) Methods: This study is reported in accordance with the CONSORT guidelines. The study aim is to assess the effectiveness of an Er:YAG laser with a wavelength of 2.94 μm, cutting and rotating instruments in the extraction of lower third molars in comparison with the traditional instruments using clinical and radiology parameters. In the control group, the impacted third molars were extracted with the traditional instruments, like scalpel and rotary instruments; in the test group, the impacted third molars were extracted with an Er:YAG laser. As per the inclusion and exclusion criteria, we enrolled 60 patients who were randomly assigned into two groups (Er:YAG laser group and control group). The efficacy of the Er:YAG laser was assessed by postoperative pain, collateral swelling, mouth opening, and radiology parameters such as radiographic infrabony defects and radiographic bone height after tooth extraction. (3) Results: The results showed that the clinical postoperative parameters like pain, collateral swelling, and mouth opening were less pronounced in the Er:YAG laser group than those in the control group (p < 0.001). According to the data of the radiology parameters (RBH and RID), the regeneration of the socket after extraction was better in the laser group than in the control group (p < 0.001). (4) Conclusions: Based on the obtained results of clinical and radiology parameters assessment, it was shown that third molar extraction using an Er:YAG laser is a less traumatic method than extraction using a scalpel and rotary instruments.